Insights into the electronic and atomic structures of cerium oxide-based ultrathin films and nanostructures using high-brilliance light sources - Luches, Paola; Boscherini, Federico (Beilstein Journal of Nanotechnology, 2025)
High-brilliance light sources, such as synchrotrons and free-electron lasers, allow researchers to probe the structural, electronic, and dynamic properties of functional materials at an unprecedented level of detail. Techniques like X-ray photoelectron spectroscopy and X-ray absorption spectroscopy, can reveal atomic-scale information about material behavior under different conditions. This thorough understanding can be leveraged to optimize materials for various applications, including energy storage, catalysis, and electronics. This review focuses on cerium oxide, an important material for catalytic and energy applications, examining the application of high-brilliance light sources on model systems such as supported thin films and epitaxial nanostructures. We review selected studies exploiting the high energy resolution and sensitivity of synchrotron radiation-based X-ray photoelectron spectroscopy and X-ray absorption spectroscopy to explain the factors influencing the material’s reducibility, with particular focus on dimensionality effects and on metal–oxide interaction, and the interaction with molecules. The potential of studies conducted under ambient pressure conditions is highlighted, and, finally, the perspectives offered by the ultrahigh brilliance and ultrashort free-electron laser pulses for dynamic studies of the processes that take place upon photoexcitation are discussed.
Keywords: cerium oxide; free-electron lasers; thin films; X-ray absorption spectroscopy; X-ray photoelectron spectroscopy